Core syntax : a minimalist approach - Adger, David (Oxford : Oxford University Press, 2003)
'Core Syntax is an introduction to the structure of sentences in human languages. Assuming no prior knowledge of linguistic theory and little of elementary grammar, it is an ideal text for students coming to syntactic theory for the first time, either as graduates or undergraduates.'--BOOK JACKET.
Includes bibliographical references : (pages. [408]-417) and index.
Keywords: Grammar, Comparative and general -- Syntax; Minimalist theory (Linguistics).